Strong Purcell enhancement at telecom wavelengths afforded by spinel Fe3O4 nanocrystals with size-tunable plasmonic properties. Issue 3 (15th December 2021) - Dolgopolova, Ekaterina A.; Li, Dongfang; Hartman, Steven T.; Watt, John; Ríos, Carlos; Hu, Juejun; Kukkadapu, Ravi; Casson, Joanna; Bose, Riya; Malko, Anton V.; Blake, Anastasia V.; Ivanov, Sergei; et al.
Abstract : Magnetite Fe3 O4 is known for its magnetic properties, but at the nanoscale it can also support a localized surface plasmon and contribute to applications in nanoplasmonics from information processing and telecommunications to light-based sensing. Abstract : Developments in the field of nanoplasmonics have the potential to advance applications from information processing and telecommunications to light-based sensing. Traditionally, nanoscale noble metals such as gold and silver have been used to achieve the targeted enhancements in light-matter interactions that result from the presence of localized surface plasmons (LSPs). However, interest has recently shifted to intrinsically doped semiconductor nanocrystals (NCs) for their ability to display LSP resonances (LSPRs) over a much broader spectral range, including the infrared (IR). Among semiconducting plasmonic NCs, spinel metal oxides (sp-MOs) are an emerging class of materials with distinct advantages in accessing the telecommunications bands in the IR and affording useful environmental stability. Here, we report the plasmonic properties of Fe3 O4 sp-MO NCs, known previously only for their magnetic functionality, and demonstrate their ability to modify the light-emission properties of telecom-emitting quantum dots (QDs). We establish the synthetic conditions for tuning sp-MO NC size, composition and doping characteristics, resulting in unprecedented tunability of electronic behavior and plasmonic response over 450 nm. In particular, with diameter-dependent variations in free-electron concentration across the Fe3 O4 NC series, we introduce a strong NC size dependency onto the optical response. In addition, our observation of plasmonics-enhanced decay rates from telecom-emitting QDs reveals Purcell enhancement factors for simple plasmonic-spacer-emitter sandwich structures up to 51-fold, which are comparable to values achieved previously only for emitters in the visible range coupled with conventional noble metal NCs.